2018
DOI: 10.1002/zaac.201800440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of RhI and IrI Complexes Supported by N‐Heterocyclic Carbene‐Phosphinidene Adducts

Abstract: N-Heterocyclic carbene-phosphinidene adducts of the type (IDipp)PR [R = Ph (5), SiMe 3 (6); IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene] were used as ligands for the preparation of rhodium(I) and iridium(I) complexes. Treatment of (IDipp)PPh (5) with the dimeric complexes [M(μ-Cl)(COD)] 2 (M = Rh, Ir; COD = 1,5-cyclcooctadiene) afforded the corresponding metal(I) complexes [M(COD)Cl{(IDipp)PPh}] [M = Rh (7) or Ir (8)] in moderate to good yields. The reaction of (IDipp)PSiMe 3 (6) with [Ir(μ-Cl)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…All four complexes display the expected square‐planar coordination spheres around the iridium atoms. The iridium‐phosphorus bonds of 2.3371(6)/2.3414(6) Å and 2.3481(4) Å in complexes 2 and 3 are slightly shorter than in the related NHC‐phosphinidene complexes [{(IDipp)PPh}Ir(cod)Cl] (2.3544(6) Å) and [{(IDipp)PSiMe 3 }Ir(cod)Cl] (2.4018(7) Å), [46] but longer than in the neutral triphenylphosphine complex [Ir(cod)Cl(PPh 3 )] (2.3041(17) Å) [47] . Upon chloride abstraction, only a slight shortening in the Ir−P bond lengths (2.3058(7)/2.2989(7) Å) is observed in complex 4 , while the Ir−P1 bond length of 2.3393(5) Å in complex 5 is almost identical to that in 3 .…”
Section: Resultsmentioning
confidence: 90%
“…All four complexes display the expected square‐planar coordination spheres around the iridium atoms. The iridium‐phosphorus bonds of 2.3371(6)/2.3414(6) Å and 2.3481(4) Å in complexes 2 and 3 are slightly shorter than in the related NHC‐phosphinidene complexes [{(IDipp)PPh}Ir(cod)Cl] (2.3544(6) Å) and [{(IDipp)PSiMe 3 }Ir(cod)Cl] (2.4018(7) Å), [46] but longer than in the neutral triphenylphosphine complex [Ir(cod)Cl(PPh 3 )] (2.3041(17) Å) [47] . Upon chloride abstraction, only a slight shortening in the Ir−P bond lengths (2.3058(7)/2.2989(7) Å) is observed in complex 4 , while the Ir−P1 bond length of 2.3393(5) Å in complex 5 is almost identical to that in 3 .…”
Section: Resultsmentioning
confidence: 90%
“… [6] In contrast, no elimination of Me 3 SiCl was observed with iridium, but instead the monometallic complex [{(IDipp)PSiMe 3 }Ir(COD)Cl] was isolated. [25] Therefore, the reactions of the silylated sulfur congener 3 with [M(COD)Cl] 2 were initially studied by NMR spectroscopy, which, depending on the stoichiometry, resulted in a clean formation of the corresponding mono‐ and bimetallic complexes 9 and 13 . However, since the preparation of the silylated educts 3 and 4 proceeded via the lithium species 1 and 2 with a significant loss of yield, they were also directly employed for the synthesis of the corresponding rhodium and iridium COD complexes 9 – 12 and 13 – 16 (Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have subsequently been reported, primarily focusing on their use as monodentate ligands . Metal carbonyl complexes of related phosphaalkenes (such as G ) showed substantially lower CO stretching frequencies in comparison to the corresponding tertiary phosphine or NHC complexes, indicating strong electron donation of these IPPs. , This was further demonstrated by the isolation of bimetallic complexes (such as H ), which illustrates the ability of these phosphaalkenes to adopt mesomeric structure B (Figure ). More recently, Tamm has reported ruthenium complexes of monoanionic phosphaalkenes, further expanding and demonstrating the scope and utility of these ligands ( I ) .…”
Section: Introductionmentioning
confidence: 89%
“…Metal carbonyl complexes of related phosphaalkenes (such as G ) showed substantially lower CO stretching frequencies in comparison to the corresponding tertiary phosphine or NHC complexes, indicating strong electron donation of these IPPs. , This was further demonstrated by the isolation of bimetallic complexes (such as H ), which illustrates the ability of these phosphaalkenes to adopt mesomeric structure B (Figure ). More recently, Tamm has reported ruthenium complexes of monoanionic phosphaalkenes, further expanding and demonstrating the scope and utility of these ligands ( I ) . Despite their attractive features as spectator ligands, coordination complexes of these IPPs have not been studied for catalytic transformations outside of olefin metathesis and 1,6-enyne cyclization. , …”
Section: Introductionmentioning
confidence: 99%